Neuroprotection by freshwater clam extract against the neurotoxin MPTP in C57BL/6 mice. (6th March 2017) - Hsieh, Cho-Chen; Lin, Muh-Shi; Hua, Kuo-Feng; Chen, Wei-Jung; Lin, Chai-Ching
Highlights: FCE promoted dopamine neuron survival in an MPTP-induced PD mouse model. FCE prevented proinflammatory responses against the neurotoxicity of MPTP. FCE stimulated the neurotrophic factors in SNpc against MPTP. Abstract: Freshwater clams are a popular health food in Asia and are traditionally used to prevent hepatic inflammation. Freshwater clam extract (FCE) inhibits inflammatory responses in activated macrophages by reducing the activation of mitogen-activated protein kinase and nuclear factor kappa-light-chain-enhancer of activated B cells. In this study, we used a mouse model of 1-methyl-4-phenyl-1, 2, 3, 6-tetrahydropypridine (MPTP; a neurotoxin)-induced Parkinson's disease (PD) to demonstrate the protective effect of FCE on dopamine neurons in the substantia nigra pars compacta (SNpc). Locomotor behavior and tyrosine hydroxylase immunohistochemical staining indicated that FCE significantly inhibited MPTP-induced dopaminergic cell loss in the SNpc. Glial fibrillary acidic protein immunohistochemistry and quantitative polymerase chain reaction analysis revealed that astroglial activation and tumor necrosis factor alpha, inducible nitric oxide synthase, and interleukin 1 beta production were significantly inhibited by FCE. The expressions of brain-derived neurotrophic factor, glial cell line-derived neurotrophic factor, and nerve growth factor were markedly increased by FCE action against MPTP-induced toxicity. FCE showed a neuroprotective effect in a MPTP-induced PD model, which might be correlated with anti-inflammation and the stimulation of neurotrophic factors.